Sero-Occurrence of HBV/HCV Co-infection and Levels of Liver Enzymes among Patients at a Tertiary Care Hospital in Central India: a Pilot Study - Prabha Desikan; Aseem Rangnekar; Zeba Khan; Nikita Panwalkar; Protiti Bose; Hanni Vasudev Gulwani; Sukhpreet Kaur (University Library System, University of Pittsburgh, 2019)
Introduction: Hepatitis B and C viral infections share common modes of transmission and account for a large proportion of liver disease burden across the globe. Patients with Hepatitis B (HBV) and Hepatitis C virus (HCV) co-infection may have more severe liver disease and are potentially at higher risk for developing hepatocellular carcinoma. The aim of this study was to assess the sero-occurrence of HBV/HCV co-infection by examining the medical records of tertiary care hospital patients in Central India and determine the extent of liver damage based on liver function tests (LFTs). Methods: Patients with a positive test for HBV surface antigen (HBsAg) over a period of 10 years were identified from laboratory records in a tertiary care facility in central India. Records of 51,075 consecutive non-duplicate blood samples were then screened for a positive HBV and HCV tests. LFT, liver enzymes, and bilirubin data were also extracted. Means and standard deviations were determined for continuous variables, and the difference in means was compared using a independent samples t-test. Associations between HBV/HCV co-infection status and demographic variables were calculated using Pearson's Chi-squared test. A p-value less than 0.05 was considered statistically significant. Results: In this study, 1674 (3.27%) screened patients were positive for HBsAg and the sero-occurrence of co-infection with HCV in HBsAg positive patients was reported in 28 individuals (1.67%). There was no significant gender difference for HBV/HCV co-infection (p>0.05). HBV/HCV co-infection was observed more frequently in the 31-60 year old age group (p=0.001). HBV/HCV co-infected patients had significantly higher levels of liver enzymes and bilirubin than those with HBsAg mono-infection (p=0.001). Conclusion: Liver function tests are potentially important predictors for HBV/HCV coinfection. Screening for HCV co-infection in HBsAg-positive patients is recommended in India. Detection of co-infection may enable timely preventive/therapeutic interventions aimed at preventing progression to hepatocellular carcinoma.